Mobile Learning Applications for Refugees: A Systematic Literature Review - Maria Drolia; Stamatios Papadakis; Eirini Sifaki; Michail Kalogiannakis (MDPI AG, 2022)
The proliferation of mobile devices in everyday life since the end of the 20th century has led to mobile applications for educational purposes and the creation of the research field of mobile learning. Despite the extended research interest on the effectiveness of this field, there is limited research on mobile learning for various social groups, such as refugees, students with learning difficulties and disabilities. Due to the unprecedented number (over one hundred million) of refugees during the second decade of the 21st century worldwide, many NGOs (Non-Governmental Organizations) and UN (United Nations) initiatives have proposed leveraging mobile learning for refugee educational needs. This research article focuses on mobile learning for refugee education. Namely, the present systematic literature review results from 2015 to 2020 will give a concrete picture of the recently existing mobile learning apps for refugees and their characteristics. According to the research findings, 15 characteristics were collected out of 14 applications. According to prior literature, areas of agreement or discrepancies in the field were found. Two new -to previous literature- characteristics were revealed: interwoven psychological and educational features and refugees' cultural features in the apps. The summarization and categorization of the app's characteristics aim to contribute to mobile learning research and impact game developers, educators, and NGOs according to refugee needs. The limitations of this study and issues for further exploration will also be discussed in the last sections.